Over Clocking Intel-i5 4670k Processor - Zaid, Shaikh; Shaikh, Zeaul; Rathod, Chaitanya; Ali, Patel; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
The Intel Core i5 4670K is a Haswell processor sporting four cores, each Over-clocked at 3.4GHz. What is new about the 4670K and differentiates it from its predecessor the i5 3570K is better power consumption, and it also offers better CPU performance, as well as improving on the GPU (Graphical Processor Unit), than the 3570K, which is a good gaming processor in itself. The processor is also capable of sustaining up to four different threads, promising good performance. Now the 4670K succeeds the 3570Kilobyte and enters the CPU charts as another great gaming processor.